Juvenile Offenders and Criminal Sanctions: A Legal Perspektive on Child Perpetrators Of Violence - Ningsih, Eci Marisna; Maryano, Maryano; Akkapin , Supaphorn (CV. Era Digital Nusantara, 2024)
This research aims to analyze criminal sanctions applied to child perpetrators of violence in Indonesia with a focus on aspects of rehabilitation and child protection. Using a qualitative approach, this study found that criminal sanctions for children are not only oriented towards punishment but also towards recovery and social reintegration. Factors that cause violence, such as family background and social environment, contribute to children's behavior. The results of this study indicate the need for a comprehensive approach to law enforcement and efforts to prevent violence among children. This research recommends improving rehabilitation programs and more effective legal protection for children in conflict with the law..